KORELASI ANTARA KEMANDIRIAN DAN KEBIASAAN BELAJAR DENGAN HASIL BELAJAR TEMATIK KELAS V SDN - Anis Saputri; Hery Kresnadi; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study aims to describe the correlation between independence and study habits with learning outcomes in the thematic learning of class V Elementary School Cluster X Sungai Kakap Kubu Raya. The research method used is descriptive in the form of correlational study research. The population in this study was the students of Elementary School Cluster X Sungai Kakap numbering 92 students. The samples in the study were 48 students who were determined by sample random sampling technique, namely the VB class 18 Elementary School Sungai Kakap totaling 22 students and the VA class 27 Elementary School Sungai Kakap totaling 26 students. The results of the study showed an average independence learning of 78.88, study habits of 80.79, and learning outcomes of 78.31. Statistical calculations using the product moment correlation formula namely learning independence with learning outcomes obtained rhitung of 0.514 and study habits with learning outcomes obtained rhitung of 0.376. For independence and study habits with learning outcomes using the multiple correlation formula obtained by 0.514 included in the category of moderate relations with Fhitung at 8.08 and Ftabel α = 5% at 3.205 which means Fhitung (8.08)> Ftabel (3,205), then Ha is accepted. So, it can be concluded that there is a relationship between independence and study habits with learning outcomes in the thematic learning of class V Elementary School Cluster X Sungai Kakap Kubu Raya. Keywords: Correlation, Learning Independence, Study Habits, Learning Outcomes, and Thematic Learning